1976
DOI: 10.1007/bf01385438
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of various bacterial strains of intestinal origin in gas-free mineral water

Abstract: Summary. We demonstrated that a washed suspension of E.coli does not subsist in Vittel mine• water more than one to four days depending on the size of the inoculum.On the other hand, P.vulgaris and especially K.pneumoniae can survive much longer in this water. Thereafter we showed that the longevity of E.coli and S.faecalis introduced into mineral water by fecal matters may be 1.5 months if the amount of feces is too small to allow multiplication of the bacteria, and 3 -4 months if the amount of feces is suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The absence of fecal indicators in samples where the pathogens were detected could be due to the fact that rapid inactivation of fecal indicators may occur in bottled water during storage. For example, Ducluzeau et al (1976) found that high numbers of E. coli ( i.e. , 10 5 –10 7 per mL) can disappear within four days, although, it has been reported that E. coli in bottled water may persist for 20 to 70 days (Burge and Hunter 1990; Obiri-Danso et al , 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The absence of fecal indicators in samples where the pathogens were detected could be due to the fact that rapid inactivation of fecal indicators may occur in bottled water during storage. For example, Ducluzeau et al (1976) found that high numbers of E. coli ( i.e. , 10 5 –10 7 per mL) can disappear within four days, although, it has been reported that E. coli in bottled water may persist for 20 to 70 days (Burge and Hunter 1990; Obiri-Danso et al , 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In a random survey of microbial quality of bottled water in South Africa, samples from 10 different brands of bottled water were tested over a period of 3 months duration and although total and faecal coliform were not detected, HPC showed a slight variation during the three-month period [21]. Other studies have shown that high counts of E.coli in bottled water could not be detected within four days [22]. The absence might be due to die-off in the bottles during storage.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated how long enteric pathogens persist when deliberately inoculated into bottled waters. Ducluzeau et al (1976a) showed that even large inocula of E. coli (10' m1-l) disappeared within 4 d in one brand of gas-free mineral water. They also demonstrated that the addition of small amounts of faeces to the bottled mineral water greatly enhanced the survival of E. coli to several weeks.…”
Section: Indicator Organismsmentioning
confidence: 99%